3D printing applied to health (Research, Society and Development, 2023)
3D printing, also known as additive manufacturing, is a technology that has existed since the 1980s. 3D printing can be applied to health in several ways: production of didactic material in the area of health, prostheses, surgical planning and with bioprinting of organs. There are several methodologies used for 3D printing applied to health, but basically they follow the process: idealization of the model, conversion of the file into STL, then G-Code and then printing and treatment of the printed object. The printers can use plastic, biodegradable material, powders, liquid or even living cells. The objective of this study is to show in a simplified way how 3D printing can be applied to health, addressing the main concepts of 3D printing. To carry out the article, a search was made for scientific articles from 2010-2023 with the theme 3D printing applied to health. This study showed that, since the 1980s, 3D printing has improved a lot, but challenges such as costs, production time and regulatory mechanisms still need to be overcome.